Micas crystal chemistry & metamorphic petrology - Mottana, Annibale; Sassi, Francesco Paolo; Thompson, James B., 1921-; Guggenheim, Stephen (Reviews in mineralogy and geochemistry ;, 2019)
Volume 46 of Reviews in Mineralogy and Geochemistry covers the international meeting on "Advances on Micas (Problems, Methods, Applications in Geodynamics)" convened in Rome in 2000. The topics of this meeting were the crystalchemical, petrological, and historical aspects of the micas. Thirteen invited plenary lectures, which consisted mostly of reviews, are presented in expanded detail in this volume. Contents:Mica crystal chemistry and the influence of pressure, temperature, and solid solution on atomistic modelsBehavior of micas at high pressure and high temperatureStructural features of micasCrystallographic basis of polytypism and twinning in micasInvestigation of micas using advanced transmission electron microscopyOptical and Mössbauer spectroscopy of iron in micasInfrared spectroscopy of micasX-ray absorption spectroscopy of the micasConstraints on studies of metamorphic K-Na white micasModal spaces for pelitic schistsPhyllosilicates in very low-grade metamorphism: Transformation to micasHistorical perspective.